Características produtivas e valor nutricional da aveia preta (Avena strigosa Schreb.) e ervilhaca comum (Vícia sativa L.) em diferentes níveis de semeadura - Banck, Adahil Roberto (2011)
Oats and vetch are the main winter crops used to cover soil in southern Brazil. Intercropping of these species can potentially result in greater productivity and forage quality than that from just the single crop. The objective of this study was to evaluate the dry matter production, botanical composition and nutritional value of oat (Avena strigosa Schereb.) and vetch (Vicia sativa L.) at different levels of sowing in intercropping systemsand single crop. The experiment was conducted at the experimental Universidade Tecnológica Federal do Paraná (UTFPR), campus Dois Vizinhos. Seeding levels tested were: A 100 – 100% 0% oats and vetch, A 75 – 75% 25% oats and vetch, A 50 – 50% 50% oats and vetch, A 25 – 25% 75% oats and vetch, A 0 – 0% 100% oats and vetch.with a density of 80 kg of seeds per hectare. The experimental design was randomized blocks with four replicates per tratament. The consortium of oats and vetch promotes an increase in dry matter yield and nutritional value of pasture. Among the ratios evaluated, 50% oats and 50% vetch, are the most suitable for promoting greater ground cover, dry matter yield and nutritional value. The proportion of 25% of oats in the consortium was the most favored the leaf / stem for vetch.